Above threshold ionization of atoms by resonant XUV laser pulses - Rodríguez Chariarse, Vladimir Daniel (2011)
Above-threshold ionization of atoms by XUV short laser pulses with frequencies close to the resonant 1s–2p transition is investigated. We present a theory based on a variational expression using trial wavefunctions for the final and the initial states. For the former we use a Coulomb–Volkov wavefunction, and for the latter a close-coupling solution of the time-dependent Schrödinger equation considering a few bound states. The close-coupling Coulomb–Volkov theory, fully accounting for the important 1s–2p transition, explains the photoelectron spectrum as well as the total ionization cross sections for the resonant case. We also compare the partial wave populations and angular distributions given by the theory with the numerical solutions of the time-dependent Schrödinger equation.